Supporting and Inhibiting Dimensions of Civilizing Process In Local Wisdom-Based Character Education - Ghufronudin Ghufronudin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
This research aimed to find out cause, form and supporting and inhibiting dimensions of character education civilizing process based on local wisdom in SMA Batik 2 Surakarta, Indonesia. The problem is focused on the character-building process informal education. To approach this problem the theoretical reference is used the civilizing process of theory by Norbert Elias. Data is collected through used were observation, in-depth interview and documentation and analyzed qualitatively.  This study concludes that there was an unprepared condition of psychogenesis and sociogenesis in the local wisdom-based character education civilizing process.  The novelty of this research is the analysis of character education based on local wisdom with the perspective of the theory of civilization Norbert Elias. The presence of local content policy in school curriculum structure, adequate school infrastructure, and supporting school and foundation management served to be the main supporting dimension. Internal inhibiting dimension included the school stakeholders’ poor awareness of understanding and implementing local wisdom value in daily life and poor synergy in cultural local content learning in organizing and developing teaching material. External inhibiting dimension included no government regulation governing the integration of local wisdom content into every subject, less optimum role and cooperation of social environment, and parents’ low commitment to supporting the process of civilizing character education based on local wisdom.